2021
DOI: 10.1111/are.15708
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐ Vibrio activity of Pseudoalteromonas xiamenensis STKMTI.2, a new potential vibriosis biocontrol bacterium in marine aquaculture

Abstract: Vibriosis is a prevalent disease in almost all mariculture species worldwide. The pathogens causing this disease can survive freely in water regardless of the host and can very easily infect marine organisms in warm water (Klesius & Pridgeon, 2011). They cause the death of shrimp and marine fish (Istiqomah et al., 2020), which in turn leads to severe economic losses and becomes a major public health problem. These causative bacteria are classified as Gram-negative and opportunistic pathogens that infect the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
(91 reference statements)
0
8
1
Order By: Relevance
“…However, we did not find references associating it with sole diseases, so its presence is potentially innocuous in our communities. The genus Pseudoalteromonas has been identified as a probiotic in aquaculture with anti-Vibrio activity (Handayani et al, 2021), although our study found no negative correlations between them. Finally, Thalassobius has also been described in marine RAS communities (Michaud et al, 2009), with species characterized as aerobic chemoorganotrophic marine bacteria (Pujalte et al, 2018), justifying their role in this environment.…”
Section: Discussioncontrasting
confidence: 80%
“…However, we did not find references associating it with sole diseases, so its presence is potentially innocuous in our communities. The genus Pseudoalteromonas has been identified as a probiotic in aquaculture with anti-Vibrio activity (Handayani et al, 2021), although our study found no negative correlations between them. Finally, Thalassobius has also been described in marine RAS communities (Michaud et al, 2009), with species characterized as aerobic chemoorganotrophic marine bacteria (Pujalte et al, 2018), justifying their role in this environment.…”
Section: Discussioncontrasting
confidence: 80%
“…All strains needed to be propagated for three generations to achieve the best cell activity. The mYCFA medium was prepared as previously reported, 34,35 and the details of 2216E 36 and AB media 37 are listed in Tables S1-S3. †…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
“…1). For structure determination, the spectroscopic data ( 1 H NMR, 13 C-NMR, and MS) of the seven compounds were comprehensively compared with the previous reports (Fremlin et 6.03, s, 1H (H-5a); 5.74, dd, 1H (H-20, J = 17.2, 10.8Hz); 5.13, d, 1H (Hcis-21, J = 4.3Hz); 5.09, d, 1H (Htrans-21, J = 10.9Hz); 4.25, dd, 1H (H-3, J = 9.6, 3.6Hz); 3.77, dd, 1H (H-11a, J = 11.6, 5.5Hz); 3.53-3.39, m, 1H (H-12); 2.88, dd, 1H (H-12, J = 14.3, 9.5Hz); 2.66, s, 3H (H-23); 2.53, dd, 1H (H-11, J = 12.4, 5.6Hz); 2.17, t, 1H (H-11, J = 12.0Hz); 1.10, s, 3H (H-19b); 0.96, s, 3H (H-19a). 13…”
Section: Structure Determination Of the Compoundsmentioning
confidence: 99%
“…Currently in both clinical medicine and aquaculture, antibiotics like quinolone, tetracycline, and erythromycin have been used to control vibriosis (Handayani et al 2022). Although there are many different antibiotics, the multidrug resistance problem has emerged and caused complicated cases (FB et al 2020;Li et al 2021;Yano et al 2014).…”
Section: Introductionmentioning
confidence: 99%